Apatia, funções cognitivas e funcionalidade motora em idosos com doença de Alzheimer - Hernandez, Salma S. Soleman [UNESP]; Vital, Thays Martins [UNESP]; Garuffi, Marcelo [UNESP]; Stein, Angélica Miki [UNESP]; Teixeira, Camila Vieira Ligo [UNESP]; Costa, José Luiz Riani [UNESP]; Stella, Florindo [UNESP] (My University, 2012)
The aims of this study were to characterize the presence of apathy in patients with AD, determine the relationship between apathy, motor function and cognitive function, and to verify differences among patients stratified by level of apathy in relation to cognitive and motor abilities. Methods: A cross-sectional study was conducted of 37 patients with AD. The following tests were used: MoCA, the Frontal Assessment Battery, Verbal Fluency, Clock Drawing Test, Andreotti & Okuma Battery Tests, Sit and Reach, Resistance of Upper Limbs - AAHPERD Battery Test, Sit and Lift Chair and the Apathy domain of the Neuropsychiatric Inventory. After verifying the normality of the data distribution, comparisons were made using Student's t-test and the U Mann Whitney test; relationships were also assessed using Pearson's and Spearman's correlation coefficients. All analyses were considered to be statistically significant at a p-value of 0.05. Results: 46% of participants in this study showed mild symptoms of apathy. Significant and weak associations were found (p=0.04) between apathy and the attention domain on the MoCA and between apathy and the Walk Test. Analysis of differences in cognitive and motor functions according to participants' level of apathy revealed no significant differences for any of the variables. Conclusion: Apathy was reflected in attention and the Walk Test, suggesting these variables may be related to cognitive and functional decline in AD patients.
Apathy, cognitive function and motor function in Alzheimer's disease
Keywords: Alzheimer's disease; Apathy; Cognition; Motor activity